PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI-F SMA NEGERI 1 TILATANG KAMANG - Zumelda, Annisa (Departemen Matematika, 2023)
Mathematics learning result are basically the main goal of the learning process. However, in reality, the mathematics learning result of in class XI-F SMAN 1 Tilatang Kamang are still low. One of the efforts that can be done to ovecome these problems is by applying the Problem Based Learning (PBL) learning model. The purpose of this study was to determine wherhet the mathematics learning result of students who learing by applying PBL learning model were better than the mathematical learning result of students whose learning by applying the conventional learning model to students of class XI-F SMAN 1 Tilatang Kamang.Keywords – Problem Based Learning (PBL), Mathematics Learning Result